Education Thought Imam Zarkasyi and Relevance to the Development of Islamic Education in Indonesia - Ana Maulida Sabila; Happy Susanto; Anip Dwi Saputro (Postgraduate Program Magister Pendidikan Agama Islam, 2020)
Colonialism in a matter of centuries that accrued in Indonesia had its impact in every aspect of life, including the education of the nation's children. The pre-independence period did not provide free space for Islamic Education and led it to a setback. This dilemma Gave birth to Reformers who would revitalize the education system in Indonesia. One of them was Imam Zarkasyi, together with his two brothers KH Ahmad Sahal and KH Zainuddin Gontor Fanani by establishing Pondok Modern Darussalam (PMDG). An educational institution in the form of a boarding school that integrates the madrasa system with the boarding system, Thus making it a 'modern' in its era. This integration has implications for the application of the day accompanied by a boarding schooling system, the implementation of written and hidden curriculum and various methods adapted to the milieu by design Gontory's. With this, the thoughts of the leaders of the renewal of Islamic Education are important to study to find an ideal model of education in Indonesia. Based on the results of the study, Imam Zarkasyi's educational thinking is relevant for the development of Islamic Education in Indonesia in the aspects of the system and institutions, aims, educators, students, and the educational situation.Kolonialisme dalam hitungan abad yang terjadi di Indonesia membawa dampak tersendiri dalam setiap sendi kehidupan, tak terkecuali pendidikan anak bangsa. Masa pra-kemerdekaan tak memberikan ruang bebas bagi Pendidikan Islam dan mengantarkannya pada roda kemunduran. Dilema inilah yang melahirkan para pembaharu yang akan merevitalisasi sistem pendidikan di Indonesia. Salah satunya Imam Zarkasyi, bersama kedua saudaranya KH Ahmad Sahal dan KH Zainuddin Fanani dengan mendirikan Pondok Modern Darussalam Gontor (PMDG). Sebuah lembaga pendidikan berbentuk pesantren yang mengintegrasikan sistem madrasah dengen sistem pesantren, sehingga menjadikannya bercorak ‘modern’ pada zamannya. Integrasi tersebut berimplikasi pada penerapan day-schooling diiringi dengan boarding system, pemberlakuan written and hidden curriculum dan berbagai metode yang disesuaikan dengan milieu by design Gontory. Dengan ini, pemikiran para tokoh pembaharuan Pendidikan Islam penting untuk dikaji demi menemukan model pendidikan ideal di Indonesia. Berdasarkan hasil penelitian, maka pemikiran pendidikan Imam Zarkasyi relevan bagi pengembangan Pendidikan Islam di Indonesia dalam aspek sistem dan kelembagaan, tujuan, pendidik, peserta didik, dan situasi pendidikan.